Relevancy and role of whole-farm models in supporting smallholder farmers in planning their agricultural season. (June 2015) - Sempore, A.W.; Andrieu, N.; Nacro, H.B.; Sedogo, M.P.; Le Gal, P.-Y.
Abstract: The way a model is designed to assist farmers in their decision-making may influence how it is understood and perceived by farmers and shape interactions between farmers and model users (researcher, advisor). This study compared the strengths and weaknesses of three types of whole farm models used by researchers to assist 18 crop-livestock farmers in Burkina Faso in planning the next agricultural season. Due to its simplicity, the static simulation tool of annual farm stocks and flows led to superior changes in the farmers' knowledge and practices. The rule-based dynamic simulation tool helped the researchers grasp farmers' decision-making processes but was difficult for farmers to understand due to the discrepancy between its multi-annual time step and the farmers' short-term planning horizon. The optimisation tool stimulated more strategic discussions regarding paths to improve farm income despite a design that was distant from the farmers' reality. Highlights: Three types of models used in a farmer's decision support process are assessed. The static stock-flow simulation tool facilitates farmer learning on farm operations. The rule-based dynamic tool helps researchers grasp farmer decision-making processes. The optimisation tool stimulates discussion on paths leading to improved farm income.